Hemispheric asymmetry of the brain as a psycho-physiological basis of individual and typological features of the formation of a sense of humour - Shportun O.N. (Medičnì Perspektivi)
The article describes the psycho-physiological peculiarities of hemispheric asymmetry of the brain as the basis of individual and typological features of the formation of a sense of humour. The analysis of the impact of the functional brain hemispheric asymmetry on emotional, intellectual and physiological features of development of sense of humour in ontogeny is conducted. Analysis of studies of inter-hemispheric asymmetry of the brain makes it possible to ascertain the impact of the functioning of each hemisphere on the formation of the perception of humour. Studies show that in the process of developing of sense of humour, two functional hemispheres of the brain are involved. As the emotion of humour – is an intellectual emotion, and in the development of intelligence a lot of mental processes are involved, in the formation of humour two hemispheres of the brain are functioned. The right hemisphere is responsible for the emotional nature of humour (intonation, sound level of language, speed of response to a joke ...), the left hemisphere – for processing verbal information (content of the joke, category, purpose, content analysis ...). After analysing the research of hemispheric functional asymmetry of the human brain, its psycho-physiological and neurochemical characteristics, it can be assumed that people with more developed left hemisphere in perceiving humour are more prone to displays of gelotophilia and “right hemisphere” people – show signs of gelotophobia and katagelasticism. Examining gender differences of hemisphere asymmetry of the brain, it can be argued that diagnosing sense of humour is important to take into account gender-specific functioning of hemispheres, because men have more clearly functioning the left hemisphere, and women – the right one. This fact of sexual peculiarities of functioning of inter-hemispheric asymmetry of the brain allows diagnosing objectively sense of humour, as well as different variations of the human psyche.